Past, Present, and Future of Gastrointestinal Microbiota Research in Cats - Lyu, Yang; Su, Chunxia; Verbrugghe, Adronie; Van de Wiele, Tom; Martos Martinez-Caja, Ana; Hesta, Myriam (Frontiers in Microbiology, 2020)
The relationship between microbial community and host has profound effects on animal health. A balanced gastrointestinal (GI) microbial population provides nutritional and metabolic benefits to its host, regulates the immune system and various signalling molecules, protects intestines from pathogen invasion and promotes a healthy structure and optimal function of the intestines. With expeditious development of next generation sequencing, molecular techniques have become standard tools for research of microbiota and demonstrated a complex and diverse intestinal ecosystem. Similar to results from other mammals, the vast majority of GI microbiota in cats (over 99%) is composed of the predominant bacterial phyla, Firmicutes, Bacteroidetes, Actinobacteria and Proteobacteria. Many nutritional and clinical studies revealed that several different factors and conditions can alter cats' microbiota, including body condition, age, diet and nutrients, inflammatory disease and others. Further research is warranted to determine functional variations of microbiome in disease states and the response to environmental and dietary modulations, to explain the intricate relationship between GI microbiota and genetics and immunity of its host, and also to improve the existing as well as the future molecular techniques. This review focusing on feline GI microbiota, summarises past and present knowledge and looks into the future prospects.